Genetic development of Stx phage - TESSA SJAHRIANI; MALA KURNIATI; DEBI ARIVO; DWI MARLINA SYUKRI; WIWIEK TYASNINGSIH (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Sjahriani T, Kurniati M, Arivo D, Syukri DM, Tyasningsih W. 2023. Genetic development of Stx phage. Biodiversitas 24: 4334-4341. Stx phages have been studied and described due to their involvement in shigatoxin. The variety, evolution, dispersion, and molecular mechanisms of STEC and Stx phages have all been widely studied, but the further research is still required. The objective of this study was to investigate the unique sequences of bacteriophage DNA from the NCBI database and to identify the changes in the DNA sequence of both regular and stx-carrying bacteriophages. It was first reported in 2001, but studies have not been carried out. The stx-carrying bacteriophage DNA sequence, similarity of identity, e-value, and gaps were analyzed using PCR and DNA sequencing. The number of bacteriophage that used in this study was eight. The results revealed the similarity of bacteriophage to stx-carrying bacteriophages by 82.67% to 88.5%, and exhibited notable variations in comparison to each phage 1 to 8 (Eco157 phage WASJ/2022) (p<0.001). Moreover, results exhibited an e-value ranging from 7e-85 to 3e-44. In addition, results showed gaps between 1-2% in comparison to other stx-carrying bacteriophages in NCBI with bacteriophage alterations on the bases of Cytosine and Thymine in 184th and 263rd. Therefore, this work provided the potency of bacteriophage as an alternative pharmaceuticals in controlling foodborne diseases.